Análise fisiológica e metabolômica de plantas de arroz sob condições de hipóxia e salinidade - Viana, Jesimiel da Silva (2021)
Hypoxia and salinity are some of the most harmful abiotic stresses for plant growth and development, being very commons in soils subject to flooding. These stresses have a significant impact on the productivity and availability of cultivated areas around the world. Rice cultivation has expressive economic and social importance for Brazil, currently the largest rice producer outside the Asian continent, moving billions of dollars each year. In Brazil, there are cultivars developed for cultivation under rainfed conditions and irrigated systems, but most of the rice produced in the country is in irrigated cultivation, subject to hypoxia and salinity. Considering that tolerance to these stresses may be related to specific modulations in the metabolic profile, the objective of this work was to evaluate the performance of rice cultivars São Francisco (SF) and BRS Esmeralda (ES) to salinity and hypoxia stresses and its relationship with changes in the metabolic profile of leaves and roots. Two experiments were carried out in a completely randomized design, both with five replications. The first to characterize the impacts of salinity on the cultivars was in a 2 x 2 factorial scheme (two cultivars x two salinity levels), and the second to evaluate the impacts of changing typical hypoxia levels in an irrigated system was in a 2 x 3 factorial scheme (two cultivars x three hypoxia levels). The rice plants were submitted for ten days to salinity (0 and 80 mM NaCl) and hypoxia treatments [severe (109.4 µM of O2), moderate (171.9 µM of O2), and slight (234.4 µM of O2) hypoxia]. After that, the plants were collected 37 days after sowing and submitted to evaluations of growth and development, photosynthetic pigments, gas exchange, chlorophyll a fluorescence, inorganic ion content, and leaf and root metabolome analysis. Salinity promoted a reduction in the physiological parameters evaluated; however, the cultivars did not show differential tolerance to salinity in the tillering phase. Thus, it was only possible to observe the differentiation regarding the metabolic pattern of leaves and roots in response to salinity and indicate some biomarkers of salt stress in rice plants. Under saline conditions, 26 metabolites were differentially expressed in the leaves and five in the roots of the two cultivars, primarily amino acids and key sugars, such as fructose and ribose. In the experiment with different hypoxia levels, the highest oxygen limitation restricted growth and development. Both cultivars reduced CO2 assimilation and other gas exchange parameters under severe hypoxia. Thus, despite the rice is a species adapted to hypoxia conditions suffers from its aggravation, according to the evaluated cultivar. SF Cultivar showed the best plasticity of response to hypoxia levels, noting a clear difference in the metabolic profile of roots between plants under severe and moderate hypoxia. Thus, this cultivar mitigated the damage caused by severe hypoxia, stimulating glycolysis and the citric acid cycle in its roots.